The Creativity of Moderat Teachers in Teaching on Pandemic Covid-19 at Madrasah - Hanafi Pelu; Murni Mahmud (Seminar Nasional LP2M UNM, 2021)
Abstract. This study aims to explain the creativity of Moderate Teachers in Pandemic Covid-19 at Madrasah. The methodology in this article is ethnography which explains the language, culture, customs, and habits. The result of this research is; Moderate teachers always consider a modification in formulating learning indicators and objectives in the moderation itself in pandemic Covid-19. Moderate teachers in formulating learning indicators and objectives, always fair, do not take sides with one or a group of students, are adjusted to conditions that are suitable for students and the school environment and facilities, are not excessive, and stay away from goals that can lead to violence.Keywords; Moderate Teachers, Teaching, Pandemic Covid-19, Madrasah